Flipped Classroom dalam Pembelajaran Matematika sebagai Alternatif Blended Learning: Sebuah Kajian Literatur - Jumini Jumini (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2022)
This literature review aimed to explore the effectiveness of Flipped Classroom in mathematics learning specifically in Indonesia through the rapid review method. It is applied to a number of former research results on the effectiveness of the Flipped Classroom in mathematics learning at junior high school, senior high school, and vocational school levels, each with 2 research results respectively. The reviewed articles were limited to research results published in national journals accredited by SINTA, from 2018 to the present to sustain the novelty and quality of the articles. The six articles were then summarized, analyzed, evaluated, and interpreted descriptively to be further synthesized and concluded to answer the purpose of the writing. The results of the study show that the Flipped Classroom method was effective in improving the learning outcomes, the concepts understanding, and the mathematical reasoning with positive effects, namely students become more active, enthusiastic, and independent in mastering the material. Thus, the Flipped Classroom method can be used as an alternative to blended learning, which can be applied during the pandemic and the new normal, to improve the quality of mathematics learning, in the cognitive, affective, and psychomotor aspects.